An Intramuscular Injection of Mixed Testosterone Esters Does Not Acutely Enhance Strength and Power in Recreationally Active Young Men - Solheim, Sara Amalie; Mørkeberg, Jakob; Juul, Anders; Freiesleben, Stine Yde; Upners, Emmie N.; Dehnes, Yvette; Nordsborg, Nikolai Baastrup (Frontiers in Physiology, 2020)
Purpose: Limited data is available on the acute performance-enhancing effects of single-dose administration of testosterone in healthy humans. Studies of testosterone administrations to healthy humans are rare due to the difficult nature and necessity of close clinical monitoring. However, our unique physiological experimental facilities combined with close endocrinological collaboration has allowed us to safely complete such a study. We tested the hypothesis that one intramuscular injection of 250 mg mixed testosterone esters enhances physical performance in strength and power exercises acutely, measured 24 h after injection. Additionally, we investigated whether the basal serum testosterone concentration influences the performance in countermovement jump, 30-s all out cycle sprint and one-arm isometric elbow flexion. Methods: In a randomized, double-blind, placebo-controlled design, 19 eugonadal men received either a testosterone ester (TE, n = 9, 23 ± 1 years, 183 ± 7 cm, 83 ± 10 kg) or a placebo (PLA, n = 10, 25 ± 2 years, 186 ± 6 cm, 82 ± 14 kg) injection. Hormonal levels and the performance in countermovement jump, 30-s all out cycle sprint and one-arm isometric elbow flexion were measured before and 24 h after injection. Results: Firstly, an intramuscular injection of 250 mg mixed testosterone esters did not enhance the vertical jump height in a countermovement jump test, peak power, mean power and fatigue index in a 30-s all-out cycle sprint, or rate of force development and maximal voluntary contraction in a one-arm isometric elbow flexion 24 h post-injection. Secondly, baseline testosterone levels appeared not to influence performance in strength and power exercises to a large extent in healthy, recreationally active young men. Conclusion: A single intramuscular injection of 250 mg mixed testosterone esters has no acute ergogenic effects on strength and power performance in recreationally active, young men. This novel information has implication for basic physiological understanding. Whether the same applies to an elite athlete population remains to be determined. If so, this would have implications for anti-doping efforts aiming to determine the most cost-efficient testing programs.